Greening Faith and Herbology in Pentecostalism in Zimbabwe - Sande, Nomatter (Journal of religion in Africa, 2019)
Abstract The role of religion in ecological discourse has gained ground in the quest to improve people’s lives in society. Herbal medicine is known to treat complex diseases. However, there are complexities in protecting the environment since herbal medicine entails having an in-depth understanding of traditional knowledge systems, beliefs, and practices. Pentecostal churches in Zimbabwe such as the Apostolic Faith Mission ( AFM ) have remained impervious to the widespread campaign promoting the use of herbs as an effective healing treatment. Divine healing is central to the AFM , and thus they view traditional herbal medicines as originating from evil spirits, despite scriptures referring to herbs as both food and medicine. Accordingly, developing a theology of ‘greening faith’ in the AFM will foster a constructive attitude toward the use of traditional herbal medicines. This article examines the position of the AFM on traditional herbal medicine and utilises ecotheology as its theoretical framework together with data gathered through in-depth interviews. The article concludes that the AFM should consciously use faith to protect the environment and promote the health and well-being of its believers.